Building heritage in Enterprise Zones: the latest threat or opportunity?. Issue 3 (8th July 2014) - Birch, Justin; Squires, Graham
Abstract : Purpose: – The purpose of this paper is to consider heritage for buildings within Enterprise Zones – a programme promoted by central government to improve the UK economy. A central view has been focusing on economic growth, with little thought given to the wider implications of heritage when imposing these zones of deregulation. Design/methodology/approach: – An illustrative case study of Bristol Temple Quarter Enterprise Zone is used that includes primary interviews with key stakeholders involved in the zone. This is synthesised with secondary literature review allowing an investigation of the way in which heritage issues are being dealt with and the resulting implications for both Bristol and in other zones in the UK. Findings: – Conflicts are demonstrated between the objectives of the Enterprise Zone scheme and those of heritage protection, indicating that they are not natural partners. It is argued that existing statutory protection is not necessarily enough to safeguard the heritage of these areas, given that the balance of power is now tipped in favour of economic growth. Originality/value: – If lessons can be learnt from this study then potential heritage issues from similar zoned developments can be avoided. The study encourages positive engagement with heritage by central government. Furthermore, it presents the first academic study that considers heritage within the latest tranche of spatially targeted fiscal incentive programmes.